ANALISIS PERENCANAAN KEBUTUHAN MATERIAL PRODUK COINT BANK PADA USAHA RADHIN HANDYCRAFT KEDIRI - Rahadian Enggar Kusuma; Bambang Agus Sumantri (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2018)
Production planning is the most important thing in running an industry. This plan is related to determining the number of products that must be produced according to the production schedule, determining the material requirements for the fulfillment of production activities effectively. Radhin Handicrafts are classified as small and medium-sized businesses making souvenirs